Continuing professional development (CPD) opportunities in Information and Communication Technology (ICT) for academic librarians at the Durban University of Technology - Underwood, Peter G. (University of Pretoria, 2019)
Mini Dissertation (MIT(Information Science))--University of Pretoria, 2017.